2021
DOI: 10.1002/ajp.23263
|View full text |Cite
|
Sign up to set email alerts
|

Not all yawns tell the same story: The case of Tonkean macaques

Abstract: Here we show for the first time that the plasticity in morphology and duration of yawning in Macaca tonkeana can be associated with different functional contexts.Macaca tonkeana is classified as a tolerant macaque species characterized by social interactions minimally constrained by dominance rank or kinship. Tonkean macaques, as other egalitarian species, rely on a complex facial communicative system.We found that the degree of mouth opening (ranging from covered to uncovered tooth yawns) and the duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 66 publications
(149 reference statements)
1
16
1
Order By: Relevance
“…During the last decades, several theories have been formulated to explain the evolutionary origins of yawning, each identifying different modulating factors as the core function of this behavioral pattern, including arousal/vigilance [1,18], brain thermoregulation [19], cortisol levels regulation [20], empathy and social interaction [3,21]. Despite this tendency to trace the origins of yawning back to a single function, recent studies have highlighted in some primates a surprising morphological and temporal variability in yawns, associated with different conditions and social contexts [22][23][24], suggesting that yawning might serve different functions in different circumstances [24].On the other hand, although these theories have been often presented as competing explanatory alternatives, several scholars have highlighted the need of distinguishing proximate and ultimate explanations when investigating mechanisms underlying the manifestation of yawning behavior [25]. In particular, advocates of the brain cooling hypothesis have argued that, while, e.g., empathy, familiarity or communication might serve as proximal mechanisms explaining yawning modulation, the ultimate function(s) of yawning is likely physiological and should be able to explain proximate mechanisms as well [26].…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, several theories have been formulated to explain the evolutionary origins of yawning, each identifying different modulating factors as the core function of this behavioral pattern, including arousal/vigilance [1,18], brain thermoregulation [19], cortisol levels regulation [20], empathy and social interaction [3,21]. Despite this tendency to trace the origins of yawning back to a single function, recent studies have highlighted in some primates a surprising morphological and temporal variability in yawns, associated with different conditions and social contexts [22][23][24], suggesting that yawning might serve different functions in different circumstances [24].On the other hand, although these theories have been often presented as competing explanatory alternatives, several scholars have highlighted the need of distinguishing proximate and ultimate explanations when investigating mechanisms underlying the manifestation of yawning behavior [25]. In particular, advocates of the brain cooling hypothesis have argued that, while, e.g., empathy, familiarity or communication might serve as proximal mechanisms explaining yawning modulation, the ultimate function(s) of yawning is likely physiological and should be able to explain proximate mechanisms as well [26].…”
Section: Introductionmentioning
confidence: 99%
“…Yawns seem to be more flexible in primates that are characterised by a high complexity in their facial musculature (Davila-Ross and Palagi 2022). In this mammalian order, the behaviour can vary in frequency, duration and motor execution as a function of the age of the subjects (Deputte 1994;Leone et al 2014) and the contexts in which the behaviour occurs (Zannella et al 2021). Further data on spontaneous yawning variability in both social carnivore and primate species are needed to understand if the phenomenon actually differs in these two lineages of mammals.…”
Section: Discussionmentioning
confidence: 99%
“…frequency, duration, morphology). It has been demonstrated that yawn variation can predict the different physiological causes on the basis of its emission (Vick and Paukner 2010;Zannella et al 2021). For example, yawning rates can be age-dependent, with juveniles yawning less than adults (Giganti and Salzarulo 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to read and appropriately interpret the signals emitted by conspecifics is an essential element for the success of sociality in humans and other highly social species ( Freeberg et al 2012 ; Demuru et al 2015 ; Arnold and Winkielman 2020 ; Casetta et al 2021 ; Nolfo et al 2021 ). Among the bodily signals produced by primates, being more dynamic, nuanced, and rapid, facial expressions represent an efficient communicative channel employed in diverse social contexts, such as aggression, sex, and play ( de Waal 1988 ; Palagi 2008 ; Cordoni and Palagi 2011a ; Chen et al 2018 ; Cordoni et al 2018 ; Palagi et al 2020a ; Zannella et al 2021 ). Having access to the face of the partner is therefore crucial to perceive and interpret their facial expressions in an appropriate way both at intra- and inter-specific level ( Palagi and Mancini 2011 ; Prochazkova and Kret 2017 ; Annicchiarico et al 2020 ; Maglieri et al 2020 ).…”
mentioning
confidence: 99%